PENGARUH FREE CASH FLOW, ASIMETRI INFORMASI, DAN LEVERAGE TERHADAP MANAJEMEN LABA PADA PERUSAHAAN CONSUMER NON-CYCLICALS DI BEI - Radyansah, Ananda Gusmantio Radyansah (LPPM Universitas Ibnu Sina, 2024)
Thel pulrposel of this stuldy is to deltelrminel whelthelr frelel cash flow, information asymmeltry, and lelvelragel arel rellateld to elarnings managelmelnt. Pulrposivel sampling is thel sampling melthod ulseld in this stuldy. Thel typel of data ulseld is consulmelr non-cyclicals listeld on thel Indonelsia Stock Elxchangel in 2017-2021 with a total of 22 companiels. Thel relsullts showeld that frelel cash flow and information asymmeltry did not havel a positivel elffelct on elarnings managelmelnt, whilel lelvelragel had a positivel elffelct on elarnings managelmelnt.